2021
DOI: 10.3390/coatings11050485
|View full text |Cite
|
Sign up to set email alerts
|

Interface between Periodontal Tissues and Dental Materials: Dynamic Changes and Challenges

Abstract: Periodontal tissues play an important role in the correct aesthetics, function and comfort of the dentition [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…As an initial requirement for clinical success, the appearance of a healthy periodontium is critical to all conservative, endodontic, and prosthetic therapies. Periodontology and restorative dentistry interact in several clinical areas, including the interface between the position of the restoration margins, the contours of the dental crown, and the subsequent response of the gingival tissues to conservative and prosthetic restorations [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an initial requirement for clinical success, the appearance of a healthy periodontium is critical to all conservative, endodontic, and prosthetic therapies. Periodontology and restorative dentistry interact in several clinical areas, including the interface between the position of the restoration margins, the contours of the dental crown, and the subsequent response of the gingival tissues to conservative and prosthetic restorations [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 summarizes the search results from this study regarding OOAC for dentistry that have been developed and investigated by several research groups. With respect to dentistry, it was found that OOAC has been used to study biofilm and saliva [ 195–211 ], dentin and pulp complex [ 212–216 ], oral mucosa [ 213–220 ], periodontal tissue [ 221–224 ], and oral malignancies [ 225–229 ]. Some other groups developed OOAC to study digestion mechanism [ 230 ], innervation [ 231 ], tooth germs and oral cell differentiation [ 232 ].…”
Section: Overview Of Organ-on-a-chipmentioning
confidence: 99%
“… To this date, the OOAC was used to study biofilm and saliva [ 187–211 ], dentin and pulp complex [ 212–216 ], oral mucosa [ 213–220 ], periodontal tissue [ 221–224 , 233 ], and oral malignancies [ 225–229 ]. Some other groups developed OOAC to study digestion mechanism [ 230 ], innervation [ 231 ], tooth germs and oral cell differentiation [ 212 , 232 ].…”
Section: Overview Of Organ-on-a-chipmentioning
confidence: 99%
See 1 more Smart Citation
“…Fixed restorations are long-term attached to the teeth with a specific dental luting cement that cannot be self-removed by the patient. Fixed prostheses come in contact with the prepared teeth abutments (especially dentin) and, respectively, their surrounding gingiva (marginal periodontium) [47]. In the case of removable partial dentures, the metal-based structure (dental base) comes into contact with the denturesupporting tissues such as the edentulous alveolar ridge and its covering masticatory mucosa and with anatomical elements such as the hard palate and its covering mucosa (the major connector of the partial removable denture) [48].…”
Section: The Oral Cavity Relationship With Prosthodontics and Implant...mentioning
confidence: 99%